Adult Children of Prisoners. An analysis of biographical experiences - Cieślikowska-Ryczko, Angelika (2023)
The study entitled Adult Children of Prisoners. Analysis of Biographical Experiences, the issue of the prison crisis of families is discussed. On the basis of the reconstruction of the biographies of adults who have experienced the incarceration of a parent, various strategies for the reconstruction of family relations were characterised, as well as the difficulties and failures associated with the interruption and loss of bonds. Assuming that the incarceration of a parent affects different spheres of functioning of adult children of prisoners, the focus was on the processual and multidimensional nature of this event in the narrators' lives. The main aim of the study was to identify and characterise the significance of the parent's incarceration in the life experiences of the narrators. The potential of biographical research, and in particular the assumptions of Fritz Schütze's biographical sociology, was used to realise this aim. In collecting and analysing empirical data, the method of autobiographical narrative interviewing was used. As a result, the monograph consists of four main parts: (1) a review of the literature on the situation, place and role of prisoners' families in the process of penitentiary isolation; (2) a theoretical-methodological study focused on the interactional research perspective; (3) an analysis of the results of own research presenting the reconstruction of narrators' biographies; and (4) an extended note on the analysis of linguistic structures.
Keywords: prison crisis, parental incarceration; rehabilitation; biographical research; narrative research; autobiographical narrative interview